(untitled) (Web of Teachers: Inderscience Research, 2026)
This article examines innovative approaches to teaching English aimed at developing learners’ creative abilities. The study analyzes the role of communicative, interactive, and digital technologies in the educational process. Special attention is paid to the effectiveness of problem-based learning, project-based methods, and collaborative learning technologies in fostering creative thinking. The research findings contribute to improving English language teaching methodology and enhancing learners’ creative competencies.